2017
DOI: 10.1101/gr.218149.116
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements are the primary source of novelty in primate gene regulation

Abstract: Gene regulation shapes the evolution of phenotypic diversity. We investigated the evolution of liver promoters and enhancers in six primate species using ChIP-seq (H3K27ac and H3K4me1) to profile cis-regulatory elements (CREs) and using RNAseq to characterize gene expression in the same individuals. To quantify regulatory divergence, we compared CRE activity across species by testing differential ChIP-seq read depths directly measured for orthologous sequences. We show that the primate regulatory landscape is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
217
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(264 citation statements)
references
References 108 publications
37
217
1
Order By: Relevance
“…Likewise, we compared LTRs to either evolutionary conserved or human‐specific liver cis ‐regulatory elements (Appendix Fig S1B). In these tests, tissue‐specific and human‐specific elements reached the best similarity scores with LTRs, in agreement with earlier observations (Trizzino et al , , ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Likewise, we compared LTRs to either evolutionary conserved or human‐specific liver cis ‐regulatory elements (Appendix Fig S1B). In these tests, tissue‐specific and human‐specific elements reached the best similarity scores with LTRs, in agreement with earlier observations (Trizzino et al , , ).…”
Section: Resultssupporting
confidence: 92%
“…We further tested whether the evolutionary age of the LTRs would affect their position relative to PEs (Appendix Fig S1G–I). Examinations of the profiles suggested that the ERV1 clade (approximately 170,000 copies) is better tolerated in the neighborhood of PEs than is the older ERVL clade (approximately 500,000 copies), in agreement with an earlier study showing that ERV1 is the most abundant LTR within cis ‐regulatory elements (Trizzino et al , ). The younger ERVKs were too few in number for the profiles to be meaningful (approximately 10,000 copies).…”
Section: Resultssupporting
confidence: 87%
“…More recently, Trizzino et al. () speculated that TEs, including L1s and Alu s, are the primary source of novelty in primate gene regulation. L1s and Alu s appeared at 16q24.1 location relatively recently during primate evolution, and substantial fraction of CNVs that they mediate are nonrecurrent.…”
Section: Discussionmentioning
confidence: 99%
“…Pairwise genetic distances of 1‐kb regions upstream of the coding sequence were calculated using mega‐cc 7 (Kumar, Stecher, Peterson, & Tamura, ) with the Kimura 2‐parameter model. Previous studies have indicated that transposons can insert in upstream regions (Butelli et al, ; Krishnan et al, ; Trizzino et al, ). To reduce the divergence bias caused by transposon insertions, we also calculated genetic distances after excluding 1‐kb regions that contain transposons.…”
Section: Methodsmentioning
confidence: 99%
“…Retained duplicate studies have indicated that transposons can insert in upstream regions (Butelli et al, 2012;Krishnan et al, 2018;Trizzino et al, 2017).…”
Section: Paralogues Orthologuesmentioning
confidence: 99%